2017
DOI: 10.1111/nmo.13265
|View full text |Cite
|
Sign up to set email alerts
|

Normative values and factors affecting water‐perfused esophageal high‐resolution impedance manometry for a Chinese population

Abstract: We established normative values for the water-perfused HRIM system for a Chinese population. Gender and anthropometric factors may affect various major HRIM parameters and should be taken into account when interpreting HRIM results in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 49 publications
1
20
1
Order By: Relevance
“…It is consistent with other studies . The DCI of water swallows in this study and other 3 normal value studies of the Chinese population seems lower than US population (mean DCI: <2000 mm Hg.s.cm and 2797.8 mm Hg.s.cm, respectively) and Brazil population (P95 of the DCI: 2779.0 mm Hg.s.cm and 4998 mm Hg.s.cm, respectively), but looks similar with British population (mean DCI: about 1300 mm Hg.s.cm, P95: about 2500 mm Hg.s.cm) . HREM normative values in different populations do exist, and it is needed to define the abnormal strength with our own thresholds.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is consistent with other studies . The DCI of water swallows in this study and other 3 normal value studies of the Chinese population seems lower than US population (mean DCI: <2000 mm Hg.s.cm and 2797.8 mm Hg.s.cm, respectively) and Brazil population (P95 of the DCI: 2779.0 mm Hg.s.cm and 4998 mm Hg.s.cm, respectively), but looks similar with British population (mean DCI: about 1300 mm Hg.s.cm, P95: about 2500 mm Hg.s.cm) . HREM normative values in different populations do exist, and it is needed to define the abnormal strength with our own thresholds.…”
Section: Discussionsupporting
confidence: 91%
“…Both studies provided normative values for liquid and viscous swallows. The third study used water‐perfusion HREM with impedance, and it only tested water swallows . We had used Sierra Scientific Instruments (SSI) solid‐state HRM system, the popularly used HREM system in China, provided the Chinese normative values of EGJ parameters for both solid and liquid bolus swallows .…”
Section: Introductionmentioning
confidence: 99%
“…The relatively high incidence of poor contractile vigor in the FHC group (27% of these subjects had a mean DCI of less than 450 mm Hg/s/cm with 5 mL water swallows) is also of interest, as little data are available regarding normal values for HRM metrics using water‐perfused catheters. Kessing et al reported a median DCI in healthy volunteers of 970 mm Hg/s/cm, while Tseng et al, in a Chinese population reported median DCI (IQR) of 799 (438‐1380) mm Hg/s/cm, which compares to corresponding values of 602 (362‐1048) mm Hg/s/cm we observed in the FHC group. The main caveat to making a direct comparison here is that those with functional heartburn and healthy subjects cannot be considered completely identical groups.…”
Section: Discussioncontrasting
confidence: 69%
“…DL : Normal DL which was reported in the original paper by Pandolfino et al . as the minimum value in the dataset has been subsequently reported as the 5th percentile in normative studies resulting in higher reference values than CC.…”
Section: Introductionmentioning
confidence: 99%
“…Only two publications on normative data with water‐perfused systems have reported the distribution of peristaltic breaks in their cohorts with the 95th percentile being 9.5 cm (median 2.3 cm) and 13.4 cm (median 2.2 cm) …”
Section: Introductionmentioning
confidence: 99%